PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP MINAT DAN HASIL BELAJAR IPS SISWA KELAS V GUGUS 1 KECAMATAN RAPPOCINI KOTA MAKASSAR - Sasmita Dien Fratiwi Syamsu; Idawat Idawat; Muhajir Muhajir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This study aims to determine the effect of the Quantum Teaching Learning Model Assisted by Audio Visual Media on the Interests and Learning Outcomes of Social Studies Students in Class V Cluster I, Rappocini District, Makassar City. This type of research is quantitative research. In this study, using a quasi-experimental type of research. The subjects used in this study were students of class V, class V, cluster 1, Rappocini sub-district, Makassar city with a total of 56 students. The instruments used in this study were data collection instruments, namely tests, questionnaires and observation sheets. The analysis technique is descriptive and inferential test (manova). Based on the results of the analysis, it is obtained that the Social Studies Learning Interest of Students Through Quantum Teaching Learning Model Assisted by Audio Visual Media Class V Cluster I, Rappocini District, Makassar City, the results of the MANOVA test of interest in learning and student learning outcomes show a significance value of 0.000. 0.000 < 0.05 then is rejected and is accepted. Based on this, it can be concluded that there is a significant influence in the use of the Quantum Teaching Learning Model Assisted by Audio Visual Media on the Interests and Learning Outcomes of Social Studies Students of Class V Cluster I, Rappocini District, Makassar City